2007
DOI: 10.1001/archopht.125.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Systemic Complement C3 Activity in Age-Related Macular Degeneration

Abstract: Objectives: To determine the role of systemic complement activation in the pathogenesis of age-related macular degeneration and to examine whether serum C3a des Arg reflects systemic complement activation, independent of individual complement component levels.Methods: Plasma complement C3a des Arg levels and a single nucleotide polymorphism at position 402 of the complement factor H gene (CFH) were determined in 3 groups of subjects: 42 subjects with early age-related maculopathy, 42 subjects with neovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 27 publications
8
73
1
1
Order By: Relevance
“…The reasons for disease specificity are unclear. Several studies have demonstrated elevated plasma levels of complement activation products (including C3a, C3d, Ba, and SC5b-9) in AMD compared with controls, indicating systemic dysregulation of complement, and implying that AMD is a systemic disease with local manifestation in the retina (38,39). This systemic component may amplify the effects of the fB polymorphism, explaining the disease specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for disease specificity are unclear. Several studies have demonstrated elevated plasma levels of complement activation products (including C3a, C3d, Ba, and SC5b-9) in AMD compared with controls, indicating systemic dysregulation of complement, and implying that AMD is a systemic disease with local manifestation in the retina (38,39). This systemic component may amplify the effects of the fB polymorphism, explaining the disease specificity.…”
Section: Discussionmentioning
confidence: 99%
“…This systemic component may amplify the effects of the fB polymorphism, explaining the disease specificity. Comparative expression levels from the fB alleles in controls and AMD are not yet available; early studies using crossed immunoelectrophoresis and radial immunodiffusion assays demonstrated a trend for higher expression from the fB 32Q allele in normal individuals (38,39) although, as with many complement components, the range around the mean was large. Decreased plasma levels of the fB 32R allele product may indicate decreased expression, or increased catabolism due to AP tickover or chronic inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…The authors speculate that the Arg80Gly polymorphism may weaken a potential interaction with CFH that, in turn, would lead to impaired regulation of C3 activation. A role for C3 activation in AMD has also been suggested because increased plasma C3a des Arg levels, a surrogate marker of complement activation, have been reported in AMD patients but without correlation to the at-risk CFH haplotypes (37).…”
Section: Discussionmentioning
confidence: 99%
“…Complement C3adesArg concentration has been found to increase in the plasma of patients with AMD compared to the age-matched controls (Sivaprasad et al, 2007). The presence of C3adesArg is an indicator of complement activation.…”
Section: Complement and Age-related Macular Degenerationmentioning
confidence: 97%